KESENIAN GONDANG SEBAGAI REPRESENTASI TRADISI MASYARAKAT PETANI DI JAWA BARAT - Rosyadi Rosyadi (Patanjala: Journal of Historical and Cultural Research, 2016)
This paper aims to reveal the existence of traditional art ofgondang which is a representation of a living tradition among the farmers in the rural areas of West Java. Gondang art stems from a tradition of ritual nutu (pound rice using a pestle and mortar) are sacred. Behind the sanctity of this tradition, there is another side that is capable of creating merriment, joy and cheerfulness, so that this tradition then elevated to an art, the art of traditional tutunggulan which is an instrumental art. Art aesthetic element is reinforced with the inclusion of singing elements. Then,gondang art is created as the development of tutunggulan art. On the appearance of gondang art, the element of the sacred has been much reduced; otherwise the entertainment element is more prominent so the gondangart becomes contemporary performing arts once highly favored by the Sundanese people, especially in rural areas. Now the existence of the art of gondangis in the middle of degraded and endangered, marginalized by the types of modern art. The method that the writer used in this research is descriptive method that relies on qualitative data.